2009
DOI: 10.4020/jhrs.25.24
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and Cytoarchitecture of Bachmann’s Bundle in the Mammalian Heart

Abstract: Recently, the Bachmann's bundle (BB) has been examined in connection with atrial fibrillation. However, the morphological properties of the BB remain to be clarified.In this study, the BB in hearts of monkeys and sheep was investigated by immunohistochemistry, scanning (SEM) and transmission (TEM) electron microscopy.Immuno-histochemically, BB myocytes showed a strong positive reaction for desmin antibody and that connexin (Cx) 40 and Cx43 were distributed at the intercalated disks. BB myocytes were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In fetal rats, strong desmin immunoreactivity was noted in the sinoatrial node, the superior caval vein, and the myocardium along pulmonary veins (Ya et al, 1997 ). Interatrial conducting pathway was reported to exhibit strong desmin immunolabeling compared to working cardiomyocytes in monkeys and sheeps (Yamaguchi et al, 2009 ). However, description of desmin expressing supraventricular structures in human adults is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In fetal rats, strong desmin immunoreactivity was noted in the sinoatrial node, the superior caval vein, and the myocardium along pulmonary veins (Ya et al, 1997 ). Interatrial conducting pathway was reported to exhibit strong desmin immunolabeling compared to working cardiomyocytes in monkeys and sheeps (Yamaguchi et al, 2009 ). However, description of desmin expressing supraventricular structures in human adults is lacking.…”
Section: Discussionmentioning
confidence: 99%